Characteristics of chest pain and its acute management in a low-middle income country: analysis of emergency department surveillance data from Pakistan. Issue 2 (December 2015) - Paichadze, Nino; Afzal, Badar; Zia, Nukhba; Mujeeb, Rakshinda; Khan, Muhammad; Razzak, Junaid
Abstract Background Chest pain is one of the most frequent causes of emergency department (ED) visits in high-income countries. Little is known about chest pain patients presenting to EDs of low- and middle-income countries (LMICs). The objective of this study was to describe the characteristics of chest pain patients presenting to emergency departments (EDs) of Pakistan and to determine the utilization of ED resources in the management of chest pain patients and their outcomes. Methods This study used pilot active surveillance data from seven major EDs in Pakistan. Data were collected on all patients presenting to the EDs of the participating sites to seek emergency care for chest pain. Results A total of 20, 435 patients were admitted to the EDs with chest pain. The majority were males (M 60%, F 40%) and the mean age was 42 years (SD+/- 14). The great majority (97%, n = 19, 164) of patients were admitted to the EDs of public hospitals compared to private hospitals and only 3% arrived by ambulance. Electrocardiograms (ECGs) were used in more than half of all chest pain patients (55%, n = 10, 890) while cardiac enzymes were performed in less than 5% of cases. Chest X-rays were the most frequently performed radiological procedure (21%, n = 4, 135); more than half of the admitted chest pain patients were discharged from the EDs and less than 1% died in the ED. Conclusion Chest pain is a common presenting complaint in EDs in Pakistan. The majority received an ECG and the use of diagnostic testing, such as cardiac enzymes, is quite uncommon.